Keragaman Tanaman Pakcoy Pada Berbagai Jenis Pupuk Organik Sistem Apung Di Lahan Rawa Lebak Di Kabupaten Hulu Sungai Utara - Erma; Nur Hafizah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2024)
Lowland swamps are lands that are periodically inundated and only used once a year. Floating cultivation can be an alternative to this land. Swamp vegetation can be utilized as organic fertilizer for planting vegetables with shallow roots such as bok choy. This study aimed to 1) determine the effect of organic fertilizer dosage on the growth and yield of bok choy on floating cultivation systems in lowland swamps; 2) Understanding the effect of types of organic fertilizers on the growth and yield of bok choy in floating cultivation systems in lowland swamps. This study used a two-factor nested design with an environmental design of a three-loop complete randomized design (CRD). The first factor was the type of organic fertilizer (J), consisting of three types, namely chicken manure (j1), water hyacinth compost (j2), and ajakan compost (j3). The second factor was the fertilizer dosage (D) which was nested in the type of organic fertilizer, consisting of 4 (four) levels, namely 15 t ha-1. The research was conducted in Sarang Burung Village, Danau Panggang District, Hulu Sungai Utara Regency from September 2019 to April 2020. Observations were made on plant height (cm), the number of leaves (blade) photosynthesis rate (plant growth rate), The results indicated that organic fertilizer types, namely chicken manure, water hyacinth compost, and ajakan compost, and organic fertilizer dosage (15 tha-1) did not affect all variables except pakcoy growt and yield because the condition of the growing media in a state of water saturation so that the decomposition process of organic matter is inhibited.